Enhancing Fourth-Grade Students' Logical Thinking in Mathematics Through Interactive Math Board Learning Media - Wulandari, Fitri; Relmasira, Stefanus Christian (Journal of Innovation and Research in Primary Education, 2025)
Mathematics education faces significant challenges in developing students' logical thinking abilities, as evidenced by Indonesia's below-average PISA performance. Traditional lecture-based instruction fails to engage students effectively, necessitating innovative interactive learning media to enhance mathematical reasoning capabilities. This study aimed to develop and evaluate the effectiveness of Math Board learning media for improving fourth-grade students' logical thinking abilities in whole number concepts up to 10,000. This research employed a Research and Development approach integrating the ADDIE framework (Analysis, Design, Development, Implementation, Evaluation) with pre-experimental design using pretest-posttest comparisons. Twenty-eight fourth-grade students from SD N Mangunsari 03 participated in the study. Data collection utilized logical thinking ability tests, classroom observations, and structured interviews. Expert validation assessed media quality, while statistical analysis using SPSS version 25 included normality testing, homogeneity testing, paired samples t-test, and N-Gain score analysis to measure improvement effectiveness. Expert validation yielded a quality score of 90.67%, categorizing the Math Board as "Very Good." Statistical analysis revealed significant differences between pretest and posttest scores (p < .000), with a mean improvement of 49.36 points. The N-Gain analysis demonstrated a mean score of 0.7996, indicating high effectiveness (79.96% improvement rate). All prerequisite tests confirmed data normality and homogeneity, validating the statistical procedures employed. The findings demonstrate that Math Board learning media significantly enhances students' logical thinking abilities, supporting theoretical frameworks from Piaget's cognitive development theory and Vygotsky's zone of proximal development. The results exceed effectiveness levels reported in previous interactive media studies, confirming the superior impact of modular board-based approaches with visual and interactive elements in mathematics education.